The equation is already is slope intercept form where you can easily point out the gradient, or the slope, and the y intercept.
y=mx+b where m is the gradient, and b is the y intercept.
Since there is no m, the gradient is 1.
The y intercept had x=0 and y=b
b in this case is 6
the y intercept= (0,6)
Answer:
The answer is 36.20 :)
Step-by-step explanation:
Answer:
(f o g)(x)= 3x + 14
(g o f)(x) = 3x + 4
Step-by-step explanation:
(f o g)(x) = f(g(x)) = f(x + 5) = 3(x + 5) - 1 = 3x + 15 - 1 = 3x + 14
(g o f)(x) = g(f(x)) = g(3x - 1) = 3x - 1 + 5 = 3x + 4
(10(1-(1/2)^5)/1-(1/2) =
20(1-1/32)
=155/8